Postoperative Pain Comparison Between Open Hemorrhoidectomy and Stapled Hemorrhoidopexy on Internal Hemorrhoid at Siloam Hospitals Lippo Village - Sudirman, Taufik; Wiguna, Alvin Leonard (Fakultas Kedokteran Universitas Pelita Harapan, 2023)
Background: Hemorrhoids have a prevalence of 4,4%. Surgery is one of the modalities for treating hemorrrhoids. The method accepted as the